2013
DOI: 10.1186/1471-2296-14-197
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in time to diagnosis of cancer: a systematic review

Abstract: BackgroundMinimising diagnostic delays in cancer may help improve survival. Ethnic minorities have worse outcomes in some cancer types when compared to the majority; this may relate in part to differences during the diagnostic phase. Only a few British studies have specifically explored this relationship, and no synthesis of these exists. The present study aimed to systematically review evidence on ethnic inequalities in cancer diagnosis, focussing on patient and primary care intervals of diagnosis.MethodsSix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
4
30
1
Order By: Relevance
“…This result, coupled with the earlier finding that Indigenous compared with non‐Indigenous women were more likely to attend BreastScreen for the first and second time in 2015, suggests that Indigenous women are engaging with initial screening in the NT, where culturally and linguistically appropriate strategies have been implemented to meet the needs of Indigenous peoples 8 . However, our results also imply that continued attendance beyond three visits may wane with those for whom English is not the main spoken language, a finding supported by other researchers who have shown that language can be a significant barrier to health for many Indigenous cultures around the world 10,13,33,34 . For example, it is reported that there is no word for cancer in many Indigenous languages, including Australian languages, which immediately presents difficulties when promoting screening 35 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result, coupled with the earlier finding that Indigenous compared with non‐Indigenous women were more likely to attend BreastScreen for the first and second time in 2015, suggests that Indigenous women are engaging with initial screening in the NT, where culturally and linguistically appropriate strategies have been implemented to meet the needs of Indigenous peoples 8 . However, our results also imply that continued attendance beyond three visits may wane with those for whom English is not the main spoken language, a finding supported by other researchers who have shown that language can be a significant barrier to health for many Indigenous cultures around the world 10,13,33,34 . For example, it is reported that there is no word for cancer in many Indigenous languages, including Australian languages, which immediately presents difficulties when promoting screening 35 .…”
Section: Discussionsupporting
confidence: 77%
“…In addition, systematic barriers to screening are also evident for Indigenous Australians, including geographic isolation, lack of means of transportation to attend services, and a shortage of culturally competent facilitators to screening 11,12 . Evidence in the US, Canada, Alaska, Pacific Islands, and New Zealand show that Indigenous women are more likely to be underrepresented in breast screening 13–15 and have higher breast cancer mortality rates compared with non‐Indigenous women 14–16 . A similar scenario is reported for Indigenous Australian women who, despite lower breast cancer incidence, have poorer health outcomes and higher rates of death from breast cancer when compared with other Australian women 17 .…”
mentioning
confidence: 84%
“…This highlight the importance of symptom appraisal as reported in other studies [5,41,42]. Appraisal is defined as a decision making process [43] which begins when the women discovered an abnormality in their breasts [44].…”
Section: Discussionmentioning
confidence: 78%
“…There is some evidence to suggest longer CRC diagnostic delay for ethnic minorities [ 20 ], and considerable research to indicate differences in physician-patient communication based on race/ethnicity, including less provision of biomedical information, less psychosocial counseling, and less relationship building with non-White breast cancer patients [ 21 ], as well as less patient-centered communication and less positive affect towards African American patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%